2007
DOI: 10.1097/00124784-200701000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Immunization Information Systems National Research and Evaluation Agenda

Abstract: Immunization Information Systems (IIS) are operational in most states and are useful in programmatic and clinical assessments. To ensure that IIS reach their technical and usability potential, and to promote their use, we conducted a Delphi survey to develop a national IIS research and evaluation agenda. Experts with a wide range of IIS knowledge were asked to generate research and evaluation topics that document their utility in achieving and sustaining clinical and public health goals. Topics were then colla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…A lack of adequate information from vaccine providers regarding the vaccination status of each child to whom they should administer the recommended vaccines can significantly influence vaccination coverage, and it has been shown that the use of computerized, population‐based systems that collect and consolidate vaccination data is essential to this end . These systems not only support clinical decision making and provide vaccination coverage reports, but they can also help in vaccine inventory management and have the ability to generate RR messages.…”
Section: Health System Barriersmentioning
confidence: 99%
“…A lack of adequate information from vaccine providers regarding the vaccination status of each child to whom they should administer the recommended vaccines can significantly influence vaccination coverage, and it has been shown that the use of computerized, population‐based systems that collect and consolidate vaccination data is essential to this end . These systems not only support clinical decision making and provide vaccination coverage reports, but they can also help in vaccine inventory management and have the ability to generate RR messages.…”
Section: Health System Barriersmentioning
confidence: 99%
“…They have been promoted by immunization advisory bodies in the USA and Canada [17-20], and have been proposed as an alternative source of immunization status verification for the National Immunization Survey conducted annually in the USA [21]. However, it has been recognized that additional validation studies are needed to determine the accuracy of registry data and identify areas for improvement [1,16,21,22]. …”
Section: Introductionmentioning
confidence: 99%
“…Previous research agendas in the area of public health IS noted the importance of attending to user needs 37,38. With a few exceptions (for example1,16) specific public health user perceptions or needs were not at the forefront of the reviewed literature.…”
Section: Discussionmentioning
confidence: 99%